Resilience and adaptive capacities of societies: social and cultural strategies - Francesca Cubeddu; Elvira Martini (Frontiers in Sociology)
The concept of resilience is a topic that has returned to the forefront of social system analysis, especially with regard to the way in which communities react and how they can be a driving force for social reactivation as a dynamic process involving positive adaptation in the face of significant adversity. Communities have always played a fundamental role in social construction and in the implementation of actions for growth and social regulation. The same relational dynamics determined by the community involve the construction of resilience processes that guide individuals in the manifestation of their choices. The mechanisms that determine community dynamics are provided by social culture, which in turn determines both the mechanisms of resilience and those of social empowerment for community development and the possibility of creating and spreading innovation. This paper aims to analyze the concept of resilience as a social and cultural strategy of a community or group to cope with various social problems. For this reason, the text will be divided into two parts: a first theoretical part where the concept of resilience and its strategies will be defined, and a second part where, through the analysis of case studies on different social issues, we will observe how different communities have reacted and what kind of actions they have taken to restore their social functions through change and adaptation.